Effect of tack coat dosage and temperature on the interface shear properties of asphalt layers bonded with emulsified asphalt binders. (15th June 2017) - Hu, Xiaodi; Lei, Yong; Wang, Hainian; Jiang, Pei; Yang, Xu; You, Zhanping
Graphical abstract: Highlights: The interface characteristics depend on tack binder type and temperature. The favorable flowability of tack binder is crucial for the shear strength. The high viscosity of residual binder enhanced the interface shear strength. The high dosage of tack binder improved the shear properties at low temperatures. Abstract: The shear strength of the interface of asphalt concrete structure has a great influence on the mechanical properties and durability of asphalt pavement. This paper describes the experimental design and analysis of the shear properties of the interface between asphalt layers. A self-designed device was employed to measure the direct shear strength of the interface with the aid of the Universal Test Machine (UTM-100). The effect of temperature, dosage of tack coat and type of tack coat on the shear properties of the interface were studied through laboratory testing. Two types of emulsified asphalt binders, namely PC-3 and HV, were selected as the tack coats. The property was evaluated in three tack coat dosages (0.25 Kg/m 2, 0.5 Kg/m 2 and 0.75 Kg/m 2 based on residual binder) and at four test temperatures (−10 °C, 0 °C, 25 °C and 50 °C). Hence, a total number of 72 composite specimens made of AC-13 and AC-20 were subjected to the shear test to evaluate the interface shear characteristics in terms of interface shear strength, the shear failure displacement and the coefficient of interface bonding at the initial stage of shear. The results showed that the shear strength at the interface decreases gradually with increasing temperature. The least failure shear displacement of all specimens was observed at the highest temperature of 50 °C. Moreover, the results indicated that the brittleness at low temperatures, the flowability at intermediate temperatures, and the viscosity at high temperatures of tack binder have the most significant effects on the shear property of the interface of asphalt pavement.